2017
DOI: 10.5620/eht.e2017005
|View full text |Cite
|
Sign up to set email alerts
|

Are children with asthma in South Korea also associated with vitamin D deficiency?

Abstract: Recently, epidemiologic studies have shown that the lack of serum vitamin D levels may be associated with high asthma prevalence, but its effect is still controversial, depending on season, area, and food consumption. We aimed to examine the association of serum vitamin D levels with the prevalence of pediatric asthma in Korea. A total of 80 children (50 asthmatic children and 30 healthy controls) aged 6-14 years were participated in this study. Serum vitamin D levels were measured and compared between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
1
4
1
1
Order By: Relevance
“…Serum vitamin D levels are influenced by environmental factors such as age, body fat, amount of melanin, and time spent outdoors, which is why this current study examined failure to thrive and stature [6]. However, the findings in the current study are different than other studies, which found no significant difference in BMI between their control and asthmatic group, while another found that vitamin D insufficiency was associated with a higher BMI [2,9].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Serum vitamin D levels are influenced by environmental factors such as age, body fat, amount of melanin, and time spent outdoors, which is why this current study examined failure to thrive and stature [6]. However, the findings in the current study are different than other studies, which found no significant difference in BMI between their control and asthmatic group, while another found that vitamin D insufficiency was associated with a higher BMI [2,9].…”
Section: Discussioncontrasting
confidence: 83%
“…Esfandiar et al presented similar findings, in which 73.9% of a group of children with asthma were vitamin D deficient [3]. Another study conducted in Korea also found that 86% of asthmatic children showed vitamin D deficiency, whereas 28% of non-atopic children had deficient levels [2]. Further, the current study revealed that 34.21% of children in the vitamin D insufficient group failed to thrive and approximately 28.94% of children had short stature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the inclusion and exclusion criteria, a total of 35 studies were finally included in our meta-analysis. Among them, 24 studies were analyzing the association between 2, 5-OHD level and the occurrence of asthma (Alyasin et al, 2011;Awasthi & Vikram, 2014;Bai & Dai, 2018;Bener et al, 2014;Chinellato et al, 2011;Esfandiar et al, 2016;Han et al, 2017;Han et al, 2018;Hatami et al, 2014;Havan et al, 2017;Hennessy et al, 2018;Kang et al, 2018;Khan et al, 2014;Kim et al, 2017;Menon et al, 2012;Mirzakhani et al, 2018;Munkhbayarlakh et al, 2019;Omole et al, 2018;Ozkars et al, 2019;Ozturk Thomas et al, 2019;Pollard et al, 2017;Reinehr et al, 2018;Thorsteinsdottir et al, 2020;Wawrzyniak et al, 2017), and 12 studies were evaluating the effect of vitamin D supplement in treating asthma (Bar Yoseph et al, 2015;Baris et al, 2014;Jensen et al, 2016;Kang et al, 2018;C. P. Kerley et al, 2016;Litonjua et al, 2020;Paweł Majak et al, 2011;P.…”
Section: Literature Selectionmentioning
confidence: 99%
“…Asthma treatment is costly, interferes with learning, and has a high disease burden [1]. While genetic factors are related to the incidence of childhood asthma, environmental factors and daily habits are also important [2,3]. Thus, early diagnosis and treatment are necessary to prevent asthma and its exacerbations [4].…”
Section: Introductionmentioning
confidence: 99%